2017
DOI: 10.22271/tpr.2017.v4.i1.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different nitrogen forms on growth, phenolics, flavonoids and antioxidant activity in amaranth species

Abstract: Abstract:Higher plants, accumulate large number of polyphenolic compounds which are believed to act as defence compounds against different environmental constraints. Nitrogen (N) is a critical element for plant growth, absorbed as (NH 4 + ) and (NO 3 -), which affects plant growth and to some extent contributes to secondary metabolites accumulation. Greenhouse experiment was carried out to determine the effect of N forms on growth and phytochemical accumulation in Amaranthus species. Two amaranth varieties; AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
4
23
2
Order By: Relevance
“…Comparing to the nitrogen level in soils, most of the soils in the locations studied were in low nitrogen level. This is concurrent with the results by Munene, Changamu, Korir, & Joseph (2017), reported that accumulation polyphenol and flavonoid contents found in plant tissue will enhance under restricted nitrogen nutrition. Soil pH also played an important role for medicinal plants.…”
Section: Factors Affecting Phytochemical Composition Of C Nutanssupporting
confidence: 91%
“…Comparing to the nitrogen level in soils, most of the soils in the locations studied were in low nitrogen level. This is concurrent with the results by Munene, Changamu, Korir, & Joseph (2017), reported that accumulation polyphenol and flavonoid contents found in plant tissue will enhance under restricted nitrogen nutrition. Soil pH also played an important role for medicinal plants.…”
Section: Factors Affecting Phytochemical Composition Of C Nutanssupporting
confidence: 91%
“…It is known that plants in unstressed conditions absorb nitrogen mainly in its ammonium and nitrate forms, both the form of available nitrogen and the amount absorbed by the plant have an important effect on photosynthesis, growth and quality of the plant [ 15 ]. Previous works have shown a higher tolerance to abiotic stresses in different plant species fed with different ammonium ratios [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, polyamines are involved in a wide range of biological processes in plants, including not only growth, plant development and senescence, but also providing protection to plant cells against various adverse conditions [ 14 ]. In fact, a stimulation of polyamine synthesis in plants can confer tolerance to stress [ 15 ]. Although the mechanism is not yet fully understood, it is known that the importance of polyamines lies above all in the fact that these biogenic amines are part of metabolic pathways that are interconnected with the formation of important metabolites involved in the plant’s response and signaling against stress [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strictly, the dilution effect can be considered when biosynthesis of polyphenols is at an unaltered level (contrary to CNB hypothesis), with a simultaneous increase of biomass production. Moreover, it should be mentioned that beyond nitrogen nutrition, accumulation of phenolics also depending on many other nutritional, environmental, genetic, and agronomic factors …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should be mentioned that beyond nitrogen nutrition, accumulation of phenolics also depending on many other nutritional, environmental, genetic, and agronomic factors. 23,24,27 Although analysis of bioactive compounds in CE is commonly used for predicting the biological significance of plant materials, some previous work indicated that the digestion process leads to changes in phenolic profiles and in their activity. 17,[28][29][30] In this study, therefore, the in vitro digestion model was applied to determine potential bioaccessibility and activity phytochemicals and to gain a better understanding of the pro-health potential of Greek oregano affected by nitrogen fertilization.…”
Section: Discussionmentioning
confidence: 99%